Taurine improves obesity‐induced inflammatory responses and modulates the unbalanced phenotype of adipose tissue macrophages. Issue 12 (12th August 2013) - Lin, Shan; Hirai, Shizuka; Yamaguchi, Yuko; Goto, Tsuyoshi; Takahashi, Nobuyuki; Tani, Fumito; Mutoh, Chikako; Sakurai, Takanobu; Murakami, Shigeru; Yu, Rina; Kawada, Teruo
<x xml:space="preserve">Abstract</x> Scope It is increasingly accepted that chronic inflammation is a feature of obesity. Obesity‐induced inflammation triggers enhanced recruitment of macrophages into the adipose tissue. Depending on their phenotype, macrophages can be designated either as pro‐inflammatory M1 macrophages or anti‐inflammatory M2 macrophages. We have therefore investigated the effects of taurine, a sulfated amino acid that is abundant in seafood, on obesity‐related inflammation. Methods and results In high‐fat diet fed C57BL/6J mice, taurine treatment reduced the infiltration of macrophages and promoted an M2‐like phenotype of macrophages in adipose tissues. In addition, taurine decreased the production of inflammatory cytokines, and suppressed the development of hyperglycemia in diet‐induced obese mice. Moreover, in vitro experiments that involved bone marrow derived macrophages indicated that taurine treatment induced alternative M2 macrophage activation, and its chloride, taurine chloramines, inhibited classical M1 macrophage activation. Conclusion Our findings indicate that taurine treatment attenuates the infiltration of adipose tissue by macrophages and modulates the phenotype of macrophages, which suggest that taurine is a valuable food constituent with a potential to attenuate chronic inflammation in adipose tissue and improve obesity‐related insulin resistance.